Global Consensus Position Statement on the Use of Testosterone Therapy for Women. Issue 9 (1st September 2019) - Davis, Susan R.; Baber, Rodney; Panay, Nicholas; Bitzer, Johannes; Perez, Sonia Cerdas; Islam, Rakibul M.; Kaunitz, Andrew M.; Kingsberg, Sheryl A.; Lambrinoudaki, Irene; Liu, James; Parish, Sharon J.; Pinkerton, JoAnn; et al.
ABSTRACT: : This Statement is being simultaneously published in the journals Climacteric, Maturitas, Journal of Sexual Medicine, and Journal of Clinical Endocrinology and Metabolism on behalf of the International Menopause Society, The European Menopause and Andropause Society, The International Society for Sexual Medicine, and The Endocrine Society, respectively. This Position Statement has been endorsed by the International Menopause Society, The Endocrine Society, The European Menopause and Andropause Society, The International Society for Sexual Medicine, The International Society for the Study of Women's Sexual Health, The North American Menopause Society, The Federacion Latinoamericana de Sociedades de Climaterio y Menopausia, The Royal College of Obstetricians and Gynaecologists, The International Society of Endocrinology, The Endocrine Society of Australia, and The Royal Australian and New Zealand College of Obstetricians and Gynaecologists.